A study of the electrical fatigue behavior of lead zirconate titanate for micro-actuator application in hard disk drives - Luo, Zhenhua; Kampoosiri, Sirirat; Sonklin, Thita; Jongpinit, Watcharin; Marungsri, Boonruang; Pojprapai, Soodkhet (Taylor and Francis, 2021)
This research work reports the effect of electric field amplitude on fatigue behavior of lead zirconate titanate ceramics (PZT) for micro-actuator hard disk drive application. The soft PZT samples were subjected to bipolar electrical cyclic loads to study the fatigue behavior. The amplitudes of electric fields of 1.00, 1.25, and 1.50 kV/mm at 10 Hz of frequency were applied. Polarization-electric field (PE) loops representing fatigue degradation were demonstrated. The fatigue behavior was indicated by the alternation of the size and shape of PE loops and remanent polarization (Pr). It was found that the remanent polarization decreased significantly with the number of loading cycles. Fatigue degradation was more pronounced in greater applied field. A mathematical model for fatigue degradation was proposed in this work.
Keywords: P-E hysteresis loop; Sawyer-Tower circuit; fatigue; polarization; micro-actuator